Novel rat model of nonunion fracture with vascular deficit. Issue 4 (April 2015) - Roberto-Rodrigues, M.; Fernandes, R.M.P.; Senos, R.; Scoralick, A.C.D.; Bastos, A.L.; Santos, T.M.P.; Viana, L.P.; Lima, I.; Guzman-Silva, M.A.; Kfoury-Júnior, J.R.
Abstract: Nonunion fractures occur frequently in humans, with profound implications (medical and non-medical). Although there are numerous animal models to study pathogenesis and treatment of nonunion fractures, there is apparently the lack of a definitive model for atrophic nonunion fracture. Therefore, the objective was to develop a low-cost rat model of nonunion fracture with a vascular deficit that enabled standardized quantitative analysis of bone growth and regeneration. The model was developed with two surgeries, performed apart. The first involved osteotomy of the femur diaphysis, removal of periosteum and endosteum, isolation of the fracture site using a latex artefact (Penrose drain tube), and reduction of the fracture using an intramedullary pin, whereas the second surgery was to remove the latex artefact. Based on radiographic imaging, micro-CT and histological analyses done 125 days after the fracture was induced, there was clear evidence of atrophic nonunion fracture, without pin migration or specimen loss. Perceived advantages of this model included low cost, ease of reproducibility, lack of specimen loss, and, finally, the potential to assess bone growth and regeneration under poor vascular conditions.